THE CONCEPT OF HUMAN FIṬRAH IN ISLAMIC PHILOSOPHY OF EDUCATION: A SEMANTIC ANALYSIS IN RELATION TO THE QUR’AN - Waharjani Waharjani; Mohammad Jailani; Miftachul Huda (Sekolah Tinggi Agama Islam Sadra, 2024)
From the perspective of the Qur’an, investigating the concept of human nature becomes an intriguing subject for scientific exploration, with a particular focus on the term “muḥsin”. This word holds a wide range of interpretations within the Qur’an, encompassing both its semantic implications and its relevance to understanding humanity. This pursuit of understanding and learning within the realm of science, especially in academic lectures and research, aims to analyze the correlation between the concept of human nature and Islamic education as they relate to the Qur’an and Ilmud dilalah (the science of semantics). This research is specifically oriented towards qualitative research, utilizing a literature review approach. Data was collected from online sources through literature searches on platforms such as Google Scholar, Scopus, and Siendirect. Data analysis involved a meticulous content analysis process. The findings of this study highlight the concept of “fiṭrah” as a divine endowment bestowed upon humans by God, defining their existence. Understanding the meaning of this inherent nature is deemed essential for all individuals, ensuring that God’s gift is not squandered and that one’s full potential is developed. Islamic education plays a pivotal role in this context, serving as a guiding force that helps individuals preserve and direct their innate nature, particularly in fostering trust and confidence in Allah. It emphasizes the importance of nurturing one’s full potential. In Islam, education is not only emphasized but also intricately linked with the philosophy of science when applied to Islamic religious education. It is understood that Islam, as a holistic religion, provides comprehensive guidance and education for Muslims.